Implementing Positive Youth Development in Primary Physical Education: The Learning Trajectories of a Physical Education Department Head (Fomentar el Desarrollo Positivo de los Jóvenes en la Educación Física Primaria: Las Trayectorias de Aprendizaje de un - Fernando Santos; Cláudio Farias; Ivo van Hilvoorde; Daniel Gould; Paulo Pereira (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. To date no research has investigated the key mediation role of PE department heads in the successful implementation of Positive Youth Development (PYD) programmes. Thus, the purpose of this study was to examine the effects of a PYD-based intervention in the learning trajectory of a PE department head leading the implementation of a PYD programme. A PYD intervention was conducted over four months, which included several cycles of theoretical inputs interspersed with a series of PYD field applications. The principal participant in this study was an experienced PE department head who was supervising the work of 63 primary school PE teachers. Findings showed the PE department head progressed from a perspective of PYD as an inherent and naturally emerging outcome to an understanding of PYD as more structured programmes of activities that include a deliberate approach. Further research is needed to uncover effective mediation strategies that can best support the implementation of PYD at an institutional level.